Contribuições ao campo cultural: experienciações da museologia atualizadas e a práxis dos museus de Congonhas e de Formiga - Marília Andrade Pereira (2018)
This research has as focus the praxis and the museological reflections integrated to the patrimonialization. Its main objective is to investigate the updates of praxis and reflections in order to contribute to the knowledge of the museum phenomenon, which includes diverse tangible forms, cultural, material and immaterial expressions, and its relation with the subject, in order to underline its potential of reference cultural. In this sense, the research also aims at updating the concept of museums and expanding discussions about their roles and purposes in places such as the municipalities of Formiga and Congonhas, Minas Gerais state. From the notion of the museum as a phenomenon, the museological concepts adopted and their respective creation contexts were investigated in the reference museums of the research, Congonhas Museum and Francisco Fonseca Historical Municipal Museum. The theoretical framework of museology concomitant with the reflections, concepts, patrimonial cuts, narratives and performances of these institutions indicated that the performance of contemporary museums is increasingly focused on the museological experience and the relation of the subject to the collection. It was also concluded that the heterogeneity of the collection in the small historical municipal museums like the Francisco Fonseca, is not mere accumulation of objects without use. This collection is configured as a key to the museum's opening rather than as a problem. Narratives that contribute to the construction of the perception of reality (re) presented by the objects constitute a critical exercise in thinking and presenting current issues of localities. Thus, the function of research in museums goes beyond the objective information, historical and re-presentation of the memory of objects. The museum fulfills, in this sense, the important function of understanding emotion in objects, in visitors, in the team and in their relationships. The studies also pointed out that from the strengthening of the subject, that local museums also contribute to the well-being, health and to the integrality of the subject's experience through its integrated action and the expansion of the patrimonial domain. The museological experience can be constituted as creation of a mental field for the perception of the subject in relation to the space, world and time lived.